CAREER AND FAMILY: A STUDY OF WOMEN LEADERSHIP - Reflianto Muslim; Joni Indra Wandi (Jurnal Harkat : Media Komunikasi Gender, 2019)
Abstract. In the industrial revolution era of 4.0, A leader is no longer referring to gender differences but rather on competence  and performance. This study aimed to analyze the gender perception and its contribution to women leadership in their career and family in Surabaya. This is a quantitative study with method survey design where the data was collected by using questionnaire and ended closed interview form. Populations of this research are dual-career marriage women in Surabaya. To confirm the quantitative results, need interview sessions with all related respondents. Samples were determined by proportional random sampling amount are 449 respondents where, 103 full career women, 205 of them as part time career and 141 of them as housewives. The results showed that there is significant contribution toward women leadership character in three career model as independent variables those are full career, part time career and family duty as reviewed from gender perception. It showed that there are correlation between women leadership character with gender perception between their career and leadership character in their family.Abstrak. Era revolusi industri 4.0, seorang pemimpin tidak lagi merujuk pada perbedaan gender tetapi lebih pada kompetensi dan kinerja. Penelitian ini bertujuan untuk menganalisis persepsi gender dan kontribusinya terhadap kepemimpinan perempuan dalam karier dan keluarga mereka di Surabaya. Ini adalah penelitian kuantitatif dengan metode desain survei di mana data dikumpulkan dengan menggunakan kuesioner dan mengakhiri formulir wawancara tertutup. Populasi penelitian ini adalah wanita nikah karir ganda di Surabaya. Untuk mengkonfirmasi hasil kuantitatif, perlu sesi wawancara dengan semua responden terkait. Sampel ditentukan dengan jumlah proporsional random sampling yaitu 449 responden di mana, 103 perempuan karier penuh, 205 di antaranya sebagai karier paruh waktu dan 141 di antaranya sebagai ibu rumah tangga. Hasil penelitian menunjukkan bahwa ada kontribusi yang signifikan terhadap karakter kepemimpinan perempuan dalam tiga model karir sebagai variabel independen yaitu karir penuh, karir paruh waktu dan tugas keluarga yang ditinjau dari persepsi gender. Hal ini menunjukkan bahwa ada hubungan antara karakter kepemimpinan perempuan dengan persepsi gender antara karier dan karakter kepemimpinan mereka dalam keluarga.